Development of information technology elements for decision-making support aimed at re-structuring production at virtual instrument-making enterprises - Sobchak, Andrii; Lutai, Liudmyla; Fedorenko, Mykola (Eastern-European Journal of Enterprise Technologies, 2019)
This paper considers issues related to the re-structuring of virtual industrial enterprises, in particular the prospects for developing a virtual instrument-making enterprise (VIE). Such enterprises operate by employing external geographically distributed resources and could be flexible in terms of making a product demanded by market. We have proposed elements of information technology (IT) to support decision making on the organization of VIE operation. The IT elements include models and structures for decision making, including those aimed at the rational use of resources in the operation of VIE. The purpose of the proposed IT is to solve a task on supporting decision-making in the restructuring of production processes at virtual instrument-making enterprises based on market conditions. The need for re-structuring of production is caused by difficult conditions of market economy for small and medium instrument-making enterprises. A production program is formed on the basis of the currently existing demand for different categories of articles included in the product range of an enterprise, or correspond to the direction of VIE operation. The IT elements include models for an informational-analytical portal (IAP), as well as a block diagram for deploying and supporting a unified knowledge space, at flexible re-structuring of production according to market conditions. The IAP also includes expert systems (ES). The designed IT for a decision-making support to a VIE head would make it possible to produce the product demanded in the market and profitable in manufacture. IT could enable determining the number and types of necessary resources according to the assigned criteria, their distribution, taking into consideration a direction of production re-structuring